Indigeneity, Prisoner Visitation and Reincarceration in Australia: The Association Between Visits in Prison and Reincarceration for Indigenous and Non-Indigenous People. (10th March 2020) - Ryan, Nicole; Ackerman, Jeff; Ready, Justin; Kinner, Stuart A
Abstract: Prison visitation is believed to protect against reincarceration post-release. This research explored differences in prisoner visitation between Indigenous and non-Indigenous people, the predictors of visitation and the effects of visitation on the risk of reincarceration. Descriptive analyses, logistic regression and Cox proportional hazards models were conducted using survey and linked administrative data for 1, 238 Australian prisoners. We found that Indigenous people compared to non-Indigenous people were less likely to be visited, and travel distance decreased the likelihood of visitation for both groups. Moreover, visitation protected against reincarceration for non-Indigenous people only. Potential explanations for why visitation was not found to protect against reincarceration for Indigenous people are discussed as are potential implications for criminal justice systems that house Indigenous offenders.